2013
DOI: 10.1103/physrevlett.110.127201
|View full text |Cite
|
Sign up to set email alerts
|

Spin-Pump-Induced Spin Transport inp-Type Si at Room Temperature

Abstract: A spin battery concept is applied for the dynamical generation of pure spin current and spin transport in p-type silicon (p-Si). Ferromagnetic resonance and effective s-d coupling in Ni(80)Fe(20) results in spin accumulation at the Ni(80)Fe(20)/p-Si interface, inducing spin injection and the generation of spin current in the p-Si. The pure spin current is converted to a charge current by the inverse spin Hall effect of Pd evaporated onto the p-Si. This approach demonstrates the generation and transport of pure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
166
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 184 publications
(177 citation statements)
references
References 31 publications
7
166
3
1
Order By: Relevance
“…As Py-based structures is one of the most investigated systems for spin pumping and ISHE 14,[16][17][18][20][21][22][23] , our approach used here is useful for systems other than the (Ga,Mn)As-based one.…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…As Py-based structures is one of the most investigated systems for spin pumping and ISHE 14,[16][17][18][20][21][22][23] , our approach used here is useful for systems other than the (Ga,Mn)As-based one.…”
Section: Samplementioning
confidence: 99%
“…Thus, by measuring the d.c. electromotive force, one can determine the value of y SHE . Spin injection and detection based on spin pumping and the ISHE have been applied to a variety of material systems [13][14][15][16][17][18][19][20][21][22][23] . Recent work showed that it may be a promising tool for the generation and investigation of spin current in semiconducting materials, such as Si (refs 16,17), Ge (refs 18,19) and GaAs with n-type as well as p-type conduction 20 .…”
mentioning
confidence: 99%
“…SHE depends on the SOC and θ SH is a measure of the strength of SOC. Because of the generally accepted Z 4 dependence of SOC, measurement of θ SH has been focused on heavy elements by SHE [8] or inverse spin Hall effect (ISHE) [9][10][11][12][13][14][15], while 3d metals have rarely been studied [16,17].…”
mentioning
confidence: 99%
“…θ SH is a measure of SOC and can be calculated from [9,10,12,14], respectively, of the Cr layer, SD is the spin diffusion length of Cr, is the interfacial spin mixing conductance, P = 1.21 is a factor arising from the ellipticity of the magnetization precession [7], γ is the gyromagnetic ratio, h rf = 0.25 Oe is the rf field at P rf = 200 mW [7], and α is the Gilbert damping constant of YIG. To calculate θ SH , we first determine SD from the Cr thickness (t Cr ) dependence of V ISHE [ Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation